Influence of STAT4 gene polymorphisms in the pathogenesis of endometriosis. (19th March 2019) - Bianco, Bianca; Fernandes, Ramon Felix Martins; Trevisan, Camila Martins; Christofolini, Denise M.; Sanz‐Lomana, Carlos Millán; de Bernabe, Javier Valero; Barbosa, Caio P.
Abstract: The STAT4 gene is vital to signaling pathways in the immune response. Immunological alterations are involved in the pathogenesis of endometriosis, and STAT4 polymorphisms may be linked to disease development. This study's aim is to evaluate the possible association between four STAT4 polymorphisms (rs7601754/G > A, rs11889341/C > T, rs7574865/T > G, and rs7582694/C > G) and the pathogenesis of endometriosis in Brazilian women. This case‐control study's sample comprised 238 women with endometriosis and 201 healthy, fertile women without endometriosis (which was surgically confirmed). Genotyping was performed using the TaqMan system with a real‐time polymerase chain reaction; the genotype, allele, and haplotype frequencies were then compared between groups. A single‐polymorphism analysis revealed that the TT genotype of the rs7574865/T > G polymorphism was significantly more frequent in women with minimal or mild endometriosis than in the controls (10% vs. 5%, p  = 0.047). The CGAC, GTAT, and GTAC haplotypes were significantly more frequent in the women with endometriosis‐related infertility (5.8%, 4.1%, and 2.9%, respectively) than in the controls (2.4%, 1.1%, and 0.8%, respectively; p  = 0.020, p  = 0.011, and p  = 0.032, respectively), but the GGGC and CTAT haplotypes were significantly more prevalent in the control group (34.7% and 13.9%, respectively) than among the infertile group (26.2% and 9.1%, respectively). In addition, the CGAC haplotype was more frequently found in those with minimal or mild endometriosis (6.8%) than in the controls (2.4%, p  = 0.009), and the GTAT haplotype was more commonly found in those with moderate or severe disease (3.6%) than in the controls (1.1%, p  = 0.028). These findings suggest that STAT4 polymorphisms can influence the pathogenesis of endometriosis.